Jordanian women's experiences and constructions of labour and birth in different settings, over time and across generations: a qualitative study - Suha Abed Almajeed Abdallah Hussein; Hannah G. Dahlen; Olayide Ogunsiji; Virginia Schmied (BMC, 2020)
Abstract Background Overwhelmingly, women in Middle Eastern countries experience birth as dehumanising and disrespectful. Women's stories can be a very powerful way of informing health services about the impact of the care they receive and can promote practice change. The aim of this study is to examine Jordanian women's experiences and constructions of labour and birth in different settings (home, public and private hospitals in Jordan, and Australian public hospitals), over time and across generations. Method A qualitative interpretive design was used. Data were collected by face-to-face semi-structured interviews with 27 Jordanian women. Of these women, 20 were living in Jordan (12 had given birth in the last five years and eight had birthed over 15 years ago) while seven were living in Australia (with birthing experience in both Jordan and Australia). Interview data were transcribed verbatim and analysed thematically. Results Women's birth experiences differed across settings and generations and were represented in the four themes: 'Birth at home: a place of comfort and control'; 'Public Hospital: you should not have to suffer'; 'Private Hospital: buying control' and 'Australian maternity care: a mixed experience'. In each theme, the concepts: Pain, Privacy, the Personal and to a lesser extent, Purity (cleanliness), were present but experienced in different ways depending on the setting (home, public or private hospital) and the country. Conclusions The findings demonstrate how meanings attributed to labour and birth, particularly the experience of pain, are produced in different settings, providing insights into the institutional management and social context of birth in Jordan and other Middle Eastern countries. In the public hospital environment in Jordan, women had no support and were treated disrespectfully. This was in stark contrast to women birthing at home only one generation before. Change is urgently needed to offer humanised birth in the Jordanian maternity system,